(3eNJUQ GdajM GdoanSi aj GdaJM GdbOSi (B((3ddYeGO GdcGJH GdCUagGfi(B)s - (3eLOGdOjf Hi GdWGgQ eMeO Hf jYbhH GdajQhR GHGOi GdTjQGRis; (3GdajQhRGHGOj , eMeO Hf jYbhH Hf eMeO Hf EHQGgje Hf YeQ, eLO GdOjf (B- (3CHh WGgQ,J (B817 (3g` s ((3ehSi Hf CMeO GdRDGdi s)
(3ChdgG (B:s
(3hHYO agPG eNJUQ ai ZGjI GdGNJUGQ hbYJ Ydjg bQYI GdCbJUGQ s
(3BNQgG (B:s
(3hGdMeO ddg GdPi CeVi ef bVGFg hbOQg eG GbJVGg s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B146 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B118s
Keywords: (3GdJGQjNs